Sentiment Analysis of Electronic System Provider (PSE) Method Using Support Vector Machine - Turiyan Turiyan; Nurirwan Saputra; Ahmad Riyadi; Meilany Nonsi Tentua (Universitas Ahmad Dahlan, 2023)
The study discusses the policy issued by the Indonesian Ministry of Communication and Information on Electronic System Providers (PSE), with a special emphasis on the impact of the policy that has triggered public reactions on social media platforms. Based on the regulations that have been made, it has an impact on the public who believe that the regulation is made to take away access freedom and data privacy on digital systems used by the public. Sentiment analysis can see public opinion on the policy issued by the Ministry of Communication and Information. The data used is taken from social media which is labeled